DIGITALIZATION AS A FACTOR OF ECONOMIC SUSTAINABILITY AND EFFICIENCY OF AGRICULTURAL ENTERPRISES: STRATEGIC SOLUTIONS - BURDYAK, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article considers digitalization as one of the key factors in ensuring economic sustainability and increasing the efficiency of the functioning of agricultural enterprises in the face of modern challenges. It is emphasized that digital transformation is not only a tool for modernizing production processes, but also a strategic direction for adapting to market changes, climate risks and global competition. The author analyzed the current state of digitalization of the agricultural sector of Ukraine, identified the main barriers to the implementation of digital technologies, in particular in small and medium-sized farms. Attention is paid to innovative digital management tools, precision agriculture, Big Data, IoT, drone technologies and platform solutions that create new opportunities for increasing productivity, resource efficiency and reducing costs. The article proposes strategic approaches to the digital transformation of agricultural enterprises, taking into account the specifics of the industry, the level of digital readiness and the need to increase adaptability to external economic changes. Practical recommendations are formulated for the formation and implementation of digital strategies that can ensure long-term economic stability, competitiveness and sustainable development of agricultural business. Proposals are made for strategic digitalization solutions aimed at the systematic introduction of innovative digital technologies into the agricultural sector in order to increase the economic sustainability and efficiency of enterprises. They include the development of digital services infrastructure, increasing the digital literacy of personnel, the implementation of precision farming systems, the automation of production processes and the use of big data analytics to optimize resources. The proposed strategies also provide for active state support and the creation of favorable conditions for investment, which will ensure the sustainable development of agricultural business in the face of modern economic challenges.